PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH FISIKA SISWA SMP - Ajeng Alyyan Dini; Zulirfan '; Fakhruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to describe and find out the difference of problem solving ability of physics students between problem based learning group with conventional learning group. This type of research is a quasi-experimental, with intact group comparison design. The sample of this research is 23 students VIIIB class that is applying of problem based learning and 23 students VIIIC class that is with conventional learning. The data in this research is a score of ability of problem solving after applying of problem based learning. The data were analyzed using descriptive and inferential statistical. From inferential statistical we found that, there were a difference ability of problem solving of pysics student’s between problem based learning group with conventional learning group. The result of this research also showed that the ability of problem solving in implementation of problem based learning group in middle category with a score of 70,65, meanwhile in conventional learning group the ability of problem solving in low category with a score 60,00. Therefore, it can be concluded that the implementation of problem based laerning improved the ability of physics problem solving in light topic of VIII MTs Diniyah Putri Pekanbaru students.Key Words: problem based learning, ability of problem solving, light.